2018
DOI: 10.1016/j.ridd.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The identification of speech and language problems in elementary school: Diagnosis and co-occurring needs

Abstract: These results raise questions about whether children's language needs at age 11 are recognised in schools. The extent of co-occurrence challenges the way diagnostic categories should be used and supports the value of profiling of dimensions of need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
3
11
0
1
Order By: Relevance
“…It was also of note that there was an increased rate of poverty in the rDLD group when compared to the GP group. This reflects this wider literature showing decreased language ability in children of low-SES parents (B. Hart & Risley, 1995) and more recent literature showing poverty is a predictor of speech, language, and communication needs within the educational system (Dockrell & Hurry, 2018;Lindsay & Strand, 2016). This significant finding is of importance regarding our rDLD classification, although we are in line with the recent recommendations not to exclude children from a diagnosis dependent on environmental factors (Bishop et al, 2016).…”
Section: Group Differences In Early Risk Factors For Emotional Difficultiessupporting
confidence: 86%
See 1 more Smart Citation
“…It was also of note that there was an increased rate of poverty in the rDLD group when compared to the GP group. This reflects this wider literature showing decreased language ability in children of low-SES parents (B. Hart & Risley, 1995) and more recent literature showing poverty is a predictor of speech, language, and communication needs within the educational system (Dockrell & Hurry, 2018;Lindsay & Strand, 2016). This significant finding is of importance regarding our rDLD classification, although we are in line with the recent recommendations not to exclude children from a diagnosis dependent on environmental factors (Bishop et al, 2016).…”
Section: Group Differences In Early Risk Factors For Emotional Difficultiessupporting
confidence: 86%
“…Previous work with MCS has investigated the relationship between age 3 language ability and conduct problems and prosocial behavior at the age of 5 years (Girard, Pingault, Doyle, Falissard, & Tremblay, 2016a, 2016b. Language ability and parental concerns of language difficulties at the age of 5 years have been shown to be a risk factor for special educational needs related to speech, language, and communication needs later in development in this sample (Dockrell & Hurry, 2018). As mentioned previously, Forrest et al (2018) found that peer problems partially mediated the increased emotional difficulties found in children at risk of DLD.…”
Section: Current Studymentioning
confidence: 84%
“…Children with DLD and those with ASD raise particular levels of concern, albeit for different reasons. For children with DLD there have been concerns about identification (Dockrell and Hurry, 2018) and provision of additional speech and language therapy (Ebbels et al, 2019), while for those with ASD concerns have been raised about managing behavior (Lindsay et al, 2013) and support for difficulties in social communication (Roberts and Simpson, 2016). For both groups of children, the need for additional support, the manner in which this support is provided, the scarcity of trained professionals to work with pupils, and the limited evidence base underpinning effective interventions have raised concerns among researchers, professionals, and parents.…”
Section: Introductionmentioning
confidence: 99%
“…The ECLS-K 1998/99 eighth-grade SEN outcomes were drawn from 2006–2007, some 13 years ago, and more recent data would be of interest. Finally, many longitudinal surveys, at least in England, rely on parental report of SEN, often retrospectively, and this presents substantial challenges of under- and misreporting compared with administrative data (see Dockrell & Hurry, 2018). In summary, there is a need for a study using pupil-level data drawn from contemporary administrative records for a whole population.…”
Section: Explanations Of Ethnic Disproportionalitymentioning
confidence: 99%